Determinasi Tax Avoidance: Peran Profitabilitas, Leverage, Capital Intensity, dan Ukuran Perusahaan pada Perusahaan Sektor Energi di Bursa Efek Indonesia - Putri Rahayu Styaningrum; Erny Pratiwi (Jurnal Aplikasi Perpajakan, 2025)
This study aims to examine and analyze the influence of profitability, leverage, capital intensity, and company size on tax avoidance. The study focuses on energy sector companies listed on the Indonesia Stock Exchange during the period 2020-2024. In this study, profitability is measured using Return on Assets, and leverage is measured using the Debt to Equity Ratio. This study adopts a quantitative approach using secondary data as the primary source. Purposive sampling was used to determine the research sample, resulting in 10 companies as research objects with an observation period of 5 years. This yielded 50 sample data points. Data analysis was conducted using multiple linear regression analysis with the help of the SPSS software program, considering classical assumption tests, including normality tests, multicollinearity tests, heteroskedasticity tests, and autocorrelation tests. Meanwhile, to test the hypothesis, we used the F-test and t-test. The findings of this study indicate that profitability has a negative effect on tax avoidance, while leverage has no effect on tax avoidance. Furthermore, capital intensity has a negative effect on tax avoidance, and company size has a positive effect on tax avoidance.